Spatial distribution of the socioeconomic conditions of dairy cattle farmers in Mliwis Village, Cepogo, Boyolali - Hapsari, Muslihah Juwita; Al Hasan, Itqanul Mufti; Zarka, Aqila Ummu; Faiz, Naufal Nizar; Ningrum, Ayu Kurnia; Fikron, Muhammad Labib; Widiyatmoko, Wahyu (Humanities Horizon, 2025)
Desa Mliwis, Cepogo District, is one of the centers for dairy cattle production in Boyolali Regency. This research aims to analyze the spatial distribution of the socio-economic conditions of dairy cattle farmers in Mliwis Village, Cepogo, Boyolali. It is a quantitative study with a survey design. The research instrument used was a questionnaire. The data analysis technique used descriptive statistics and nearest neighbor analysis. The results of the study indicate that dairy farms in Mliwis Village are spread across 6 hamlets, namely Ngledok, Karanganyar, Bulukerto, Tlogomuncar, Tegalsari, and Geneng. The Nearest Neighbor value is 0.609900, indicating a clustered pattern. Farmers with income less than Rp. 2,000,000 have a value of 0.792268, indicating a clustered pattern, while those with income more than Rp. 2,000,000 have a value of 17.118163, indicating a dispersed pattern. Farmers with an education level below elementary school (SD) have a value of 6.610683, indicating a dispersed pattern, while those with an elementary school education level have a value of 0.9100336, indicating a clustered pattern. The distribution pattern of the education levels of dairy cattle farmers in Mliwis Village, based on the Nearest Neighbor results, shows that farmers with an education level below elementary school (SD), junior high school (SMP), and high school (SMA) have a dispersed pattern, while farmers with an elementary school education level have a clustered pattern. Farmers with 1-5 cows have a value of 0.543374, indicating a clustered pattern, while farmers with 6-10 cows have a value of 2.396315, indicating a dispersed pattern. Farmers who sell milk to agents have a value of 1.021488, indicating a dispersed pattern, while those who sell milk to cooperatives have a value of 0.581348, indicating a clustered pattern.